The Influence of Brand Image and Packaging on Loyalty through Customer Satisfaction : A Study of Amplang Obic Customers in Ketapang Regency - Oktaviani, Nabila; Triana, Neni (Jurnal Manajemen Bisnis, 2025)
This study aims to identify the influence of Brand Image and Packaging on Customer Loyalty for Amplang Obic in Ketapang Regency, with Customer Satisfaction as an intervening variable. The food industry is experiencing rapid growth, resulting in increased competition, which Amplang Obic faces from other producers offering similar products. To remain competitive, Amplang Obic must develop strategies to distinguish itself. The research employs an associative approach, with purposive sampling as the sample collection technique. A total of 100 respondents, all of whom are customers who purchase and consume Amplang Obic, participated in the study. Data analysis was conducted using structural equation modeling (SEM) with SmartPLS 3 software. The findings indicate that all variables meet the criteria for validity and reliability. Hypothesis testing reveals that Brand Image and Packaging have a positive and significant effect on Customer Satisfaction, although neither has a significant direct effect on Customer Loyalty. However, Customer Satisfaction positively and significantly influences Customer Loyalty. Furthermore, when mediated by Customer Satisfaction, both Brand Image and Packaging demonstrate a positive and significant effect on Customer Loyalty.